Brain and brain blood vessels histological description in autopsies of fetuses/neonates born to mothers with hypertension during pregnancy. A case–control studyResearch in context - Johana González; Jorge Anxdrés Franco; Carlos Escudero; Mercedes Olaya (The Lancet Regional Health. Americas)
Summary: Background: Children born to women with hypertension during pregnancy have a two to threefold increased risk of developing cognitive disorders compared to children born to women without hypertension. However, structural changes in the central nervous system of these children remain poorly understood. We aim to compare the brain histological findings from autopsies of neonates and fetuses born to women with and without hypertension during pregnancy. Methods: This retrospective case–control study includes brain histological samples from autopsies of neonates and fetuses born to women with (n = 22) and without (n = 15) hypertension during pregnancy, obtained from biobanks associated with the University Hospital San Ignacio (HUSI), Bogotá, Colombia, between 2007 and 2022. Hypertension during pregnancy was diagnosed following American College of Obstetricians and Gynecologists (ACOG) guidelines. Matched criteria included similar maternal pre-pregnancy morbidity, gestational ages at delivery, fetal sex, and availability of similar histological samples of fetal/neonatal brains. Clinical data were recorded, and two diagnosed-blinded pathologists analyzed all slides. Findings: Ninety-three percent (14/15) of fetuses/neonates born to women with hypertension during pregnancy were born after preeclamptic pregnancies. Histological findings were described for the frontotemporal cortex (97%, 36/37) and meninges (81%, 30/37). Fetuses/neonates born to women with hypertension during pregnancy were smaller (p = 0.030), had a lower gestational age at death (p = 0.047), and were more frequently stillborn. Autopsy records revealed higher maternal vascular malperfusion in women with hypertension during pregnancy (p < 0.0001). Subarachnoid hemorrhage was more common in fetuses/neonates born to women with hypertension during pregnancy (p = 0.036). Other frequent findings included neuropil edema, congested meninges, hypoxic-ischemic encephalopathy, subdural hematoma, venous sinus thrombosis, hemoventricle, and necrotic foci. However, no significant endothelial or vascular wall changes were noted. “Prominent and congested” capillaries were observed only in fetuses/neonates born to women without hypertension. Interpretation: The findings suggest increased cerebrovascular vulnerability in fetuses and neonates exposed to maternal hypertension during pregnancy, with a higher incidence of subarachnoid hemorrhage. While no vascular wall changes were identified, fewer brain capillary alterations were noted in those born to women with hypertension during pregnancy. Funding: Fondecyt 1200250, 1240295.